2015
DOI: 10.3390/s150818865
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Atmospheric Correction for Above-Ground Forest Biomass Estimation with the ETM+ Remote Sensor

Abstract: The reflectance of the Earth’s surface is significantly influenced by atmospheric conditions such as water vapor content and aerosols. Particularly, the absorption and scattering effects become stronger when the target features are non-bright objects, such as in aqueous or vegetated areas. For any remote-sensing approach, atmospheric correction is thus required to minimize those effects and to convert digital number (DN) values to surface reflectance. The main aim of this study was to test the three most popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 57 publications
1
35
0
3
Order By: Relevance
“…It should be taken into account that the GCV criterion considers both the residual error and also the model complexity, penalizing those models with a high number of parameters. The results are similar to those obtained by Nguyen et al [71] in a study carried out in South Korea in which it was confirmed that the 6S algorithm fitted by the kNN technique (RMSE = 22.5 Mg¨ha´1) produced better results for estimating AGB than the other algorithms tested (DOS, FLAASH and ToA), especially for Landsat ETM bands in the infrared region. Furthermore, various studies have concluded that the MARS technique is a flexible method that yields robust predictions [72,73].…”
Section: Discussionsupporting
confidence: 89%
“…It should be taken into account that the GCV criterion considers both the residual error and also the model complexity, penalizing those models with a high number of parameters. The results are similar to those obtained by Nguyen et al [71] in a study carried out in South Korea in which it was confirmed that the 6S algorithm fitted by the kNN technique (RMSE = 22.5 Mg¨ha´1) produced better results for estimating AGB than the other algorithms tested (DOS, FLAASH and ToA), especially for Landsat ETM bands in the infrared region. Furthermore, various studies have concluded that the MARS technique is a flexible method that yields robust predictions [72,73].…”
Section: Discussionsupporting
confidence: 89%
“…In comparison with other multitemporal studies [23,49,50], we have tested different CMs with a change of platform from Landsat 5 to Landsat 8 in grassland areas. In the site Eden, we found that the deviations between the estimated and measured biomass were high for 2013 and 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Martins et al [47] compared the 6S, ACOLITE, and Sen2Cor methods applied to the new platform Sentinel 2-MSI. However, these studies lack the multitemporal component and only a few studies [48][49][50] have been developed to compare the methods of radiometric correction on different dates.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al (2000) who examined Landsat 5 Data with FLAASH, Foster and 6S models found that FLAASH was the best model. Nguyen et al (2015) who reviewed QUAC, FLAASH and 6S models with Landsat 5 Data stated that 6S was the best model which resembled on ground condition. Afterall, this research aimed to analyze a suitable atmospheric correction model for Landsat OLI data in order to retrieve Indonesian land cover information which corresponded to actual coverage.…”
Section: Introductionmentioning
confidence: 99%